2010
DOI: 10.1080/02786821003652646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methanol–Biodiesel Blends on the Particulate Emissions of a Direct Injection Diesel Engine

Abstract: In this study, Euro V diesel fuel, biodiesel, and methanolbiodiesel blends were tested in a 4-cylinder direct-injection diesel engine to investigate the combustion characteristics and particulate emissions of the diesel engine under five engine loads at the maximum torque engine speed of 1800 rpm. Compared with Euro V diesel fuel, biodiesel gives lower and earlier heat release rate. For the blended fuels, the peak heat release rate becomes higher and retarded. With regard to particulate mass concentration, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…This experimental result also yielded extremely low CO and NO x emissions, which were attributed to the more completed combustion due to higher oxygen content of methanol and low combustion chamber temperature because of the methanol cooling effect. Improved engine performance by using biodiesel and methanol blend fuels can also be found in [9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…This experimental result also yielded extremely low CO and NO x emissions, which were attributed to the more completed combustion due to higher oxygen content of methanol and low combustion chamber temperature because of the methanol cooling effect. Improved engine performance by using biodiesel and methanol blend fuels can also be found in [9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…Lin et al [19] studied the particle size distribution of a diesel engine that was fuelled with palm-biodiesel blends and reported an increased number of particles with low aerodynamic diameters in biodiesel and biodiesel-diesel blends, in comparison with that of diesel. Zhu et al [20] examined the influence of methanol-biodiesel blends on particle distribution in a direct injection diesel engine and reported that the use of methanol-biodiesel blends could reduce the number concentration of all sizes, as compared with biodiesel. Park et al [21] studied nanoparticle emissions of biodiesel-diesel blends and reported that both the total number and total mass were reduced when blending biodiesel; however, the number of fine particles was observed to have increased.…”
Section: Introductionmentioning
confidence: 98%
“…Fig. 6 shows that the GMD increases with engine load for each fuel which is a consequence of the increase in mass of fuel burned in the diffusion combustion mode at high engine load (Tsolakis, 2006;Zhu et al, 2010;Srivastava1 et al, 2011). The high fuel/air ratio and local temperature associated with high engine load also promote particle formation.…”
Section: Mass-based Investigation Of Particle Volatilitymentioning
confidence: 99%